Population wellbeing and psychosocial burden during the COVID-19 Pandemic in Germany – results from (bi-)weekly monitoring data and the resulting health promoting activities on the national level. (20th October 2021) - De Bock, F
Abstract: Since march 2020, data on risk perception, behavior and psychosocial wellbeing of the population with regard to the COVID-19 pandemic have been collected regularly (biweekly to weekly) in Germany as part of the COVID-19 Snapshot Monitoring (COSMO). The data i.e. show that the psychosocial burden is higher in specific population subgroups, such as younger adults and families. Based on these data, the Federal Centre for Health Education as part of the federal government developed health promoting activities on the national level to maintain wellbeing and buffer the burden. Over the course of the pandemic, these activities changed dynamically according to the differing situation (lock-down, incidence). With the second wave, as incidences increased dramatically without vaccination available, the activities were expanded from a web-based platform 'Psychisch stabil bleiben' (Mind your mental health), supported by a nationwide telephone counseling service, to a nationwide mail distribution of postcards in five different languages, with links to the virtual platform and various telephone counselling services. The website offers information on coping strategies and psychotherapeutic services, edited for specific population groups (e.g. parents, people with preexisting mental illness, health professionals) in five different languages. The postcards were distributed through primary care providers, pharmacies and social services in socially disadvantaged geographical areas, trying to increase reach in vulnerable populations.